Development of Type 1 Diabetes may occur through a Type 2 Diabetes mechanism - Josefsen, Knud; Krogvold, Lars; Gerling, Ivan C.; Pociot, Flemming; Dahl-Jørgensen, Knut; Buschard, Karsten (Frontiers in Endocrinology, 2022)
Background At diagnosis of Type 1 Diabetes (T1D), 30% of the beta cells are dormant, i.e. alive, but inactive. This could reduce beta cell destruction, as cellular stress contributes to beta cell damage. However, the beta cells, that are still active, must produce more insulin and are therefore more vulnerable. The inactive beta cells represent a potential for restoring the insulin secretion. Methods We analyzed the expression of selected genes in islets from live, newly diagnosed T1D patients from the DiViD study and organ doners with longer duration of T1D, type 2 diabetes (T2D), or no diabetes from the nPOD study. Additionally, analysis of polymorphisms was performed on all the investigated genes. Findings Various possibilities were considered for the inactivity of the beta cells: secretion defect, fetal state, hibernation, and insulin resistance. We analyzed genes related to the ceramide and sphingomyelin synthesis and degradation, secretion, circadian rhythm and insulin action, and found changes in T1D islets that resemble fetal dedifferentiation and asynchrony. Furthermore, we found low levels of insulin receptor mRNA in the islets. No polymorphisms were found. Interpretation Our findings suggest a secretion defect, but also fetal dedifferentiation and desynchronization in the inactive beta cells. Together with previous evidence, that predisposing factors for T2D are also present for T1D development, we raise the idea to treat individuals with ongoing T1D development prophylactically with T2D medicine like GLP-1 receptor agonists, metformin, or others, combined with anti-inflammatory compounds, in order to reactivate the dormant beta cells, and to prevent autoimmune destruction. T2D mechanisms during T1D development should be investigated further.